Persepsi Santri Terhadap Program Peningkatan Literasi di Pesantren Darularafah Raya Deli Serdang, Sumatera Utara - Ella Nurwana; Retno Sayekti (Jurnal Pustaka Ilmiah, 2026)
This study aims to analyse students' perceptions of literacy improvement programs at Darul Arafah Raya Islamic Boarding School. Literacy programs implemented by the Pesantren include literacy competitions, a mobile cart library, and reading corners. This research employed a descriptive qualitative approach to explore students' experiences, responses, and participation in literacy activities. Data were collected through observation, in-depth interviews, and documentation involving 8 informants consisting of 5 junior high school students and 3 library managers selected through a purposive sampling technique. The findings indicate that literacy programs have been implemented systematically and continuously; however, students' participation remains relatively low. Students perceptions toward literacy programs vary into positive and less positive perceptions. Positive perceptions are influenced by reading interest, attractive literacy activities, and perceived benefits such as increased knowledge and learning experiences. Meanwhile, low reading interest, boredom, and limited book variety contribute to lower participation. The study concludes that students' perceptions significantly influence their involvement in literacy programs. Therefore, literacy activities in Islamic boarding schools should be designed more attractively, contextually, and aligned with students' interests to improve participation and foster a literacy culture.